The Influence of Financial Literacy and Personal Financial Attitude on Financial Behavior with Lifestyle as an Intervening Variable on Productive Generation Y in Medan City - Radiman, Radiman; Wahyuni, Sri Fitri; Lestari, Sherly (AIBPM Publisher, 2023)
Every person has unique financial habits shaped by internal and external causes. A perso’'s financial behaviour depends on their financial expertise. This study examines how financial education and attitudes towards money affect the financial decisions of productive Generation Y residents in Medan City. The lifestyle intermediate function in this link is also investigated in this research.Quantitative research approaches, such as surveys, are used in this study. Data processing was done using clever PLS software on 96 individuals. Data analysis methods including path analysis, PLS, and mediation effect analysis are popular.The research shows that financial knowledge strongly impacts lifestyle choices. Financial behaviour is heavily influenced by personal finance views. One's lifestyle is shaped by their financial views. Additionally, lifestyle might affect financial behaviour. This study also analyses how financial literacy and personal financial views affect financial behaviour and management, with lifestyle as a mediating component.